Rapra Collection of DSC Thermograms of Semi-Crystalline Thermoplastic Materials - Price, Clive (Rapra Technology Limited, 2011)
The result of many years work this book provides a set of thermograms for 68 materials covering a broad range of widely available semi-crystalline polymers.